2013
DOI: 10.1056/nejmoa1300720
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mortality after Screening for Colorectal Cancer

Abstract: The effect of screening with fecal occult-blood testing on colorectal-cancer mortality persists after 30 years but does not influence all-cause mortality. The sustained reduction in colorectal-cancer mortality supports the effect of polypectomy. (Funded by the Veterans Affairs Merit Review Award Program and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
519
1
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 732 publications
(550 citation statements)
references
References 32 publications
7
519
1
15
Order By: Relevance
“…However, this group may not be an appropriate age group to target, because it has lower CRC incidence and mortality than older groups and stratified analysis of trials of FOBT have not shown benefits of CRC screening in the 50-55 age group. 31,32 Screening of healthy individuals above the age of 75, especially those with no prior CRC screening, may be appropriate, because they have higher CRC incidence and mortality than younger individuals; 1 no CRC screening RCT has included people older than 75. Although the decreased odds of CRC screening among single men was not statistically significant in our study, the trend we observed supports findings in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, this group may not be an appropriate age group to target, because it has lower CRC incidence and mortality than older groups and stratified analysis of trials of FOBT have not shown benefits of CRC screening in the 50-55 age group. 31,32 Screening of healthy individuals above the age of 75, especially those with no prior CRC screening, may be appropriate, because they have higher CRC incidence and mortality than younger individuals; 1 no CRC screening RCT has included people older than 75. Although the decreased odds of CRC screening among single men was not statistically significant in our study, the trend we observed supports findings in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer screening significantly reduces colorectal cancer incidence and mortality, as demonstrated by large studies with a long follow-up period (1)(2)(3)(4). The Netherlands has recently implemented a colorectal cancer screening program, consisting of biennial fecal immunochemical testing (FIT) in individuals aged 55 to 75 years.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, gFOBT has limitations largely because of its reliance on detecting a more nonspecific marker for bleeding (ie, heme through a peroxidase reaction). Newer tests like FIT and sDNA have clear biological advantages over gFOBT16; however, the evidence for these tests is less mature.17 For FIT and a select few sDNA18, 19 and 20 panels, there are cross-sectional, population-based studies in which colonoscopy is the reference standard.…”
Section: Quality Of Evidencementioning
confidence: 99%